A simplified damage evolution relationship and deformation characteristics of a pozzolanic lime mortar when subjected to unloading-reloading cycles in the pre-peak region - Kostas Kaklis; Zach Agioutantis; Stelios Mavrigiannakis; Pagona Maravelaki-Kalaitzaki (Fracture and Structural Integrity)
Two series of uniaxial and triaxial compression tests including unloading-reloading cycles were performed under different confining press¬ures, in order to study the stress-strain and the deformation behavior of a pozzolanic lime mortar subjected to cyclic loading. Each test included a cyclic loading sequence using five loops in the pre-peak region. The experi¬ment¬al results showed that the specimens exhibit a strain-softening behavior for uniaxial and low pressure triaxial tests and a strain-hardening behavior for higher triaxial compression tests. The mortar specimens subjected to triaxial compressive cyclic loading at higher confining pressures failed along a single or conjugate shear planes accompanied by considerable lateral ex¬pansion. The marked Youngs modulus degradation behavior in the pre-peak region is related to damage that occurs in each specimen